TAX EFFORT DETERMINANTS: THE ROLE OF TAX STRUCTURE AND FINANCIAL DEVELOPMENT IN SOUTHEAST ASIA - Ardi Sugiyarto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
Tax revenue is vital for financing sustainable development and ensuring fiscal stability, yet several Southeast Asian countries continue to face declining collection performance. This study assesses the tax effort of eight Southeast Asian economies between 1990 and 2020, employing an empirical panel regression model to estimate tax capacity based on macroeconomic, structural, and institutional factors. The resulting tax effort (the ratio of actual to predicted tax revenue) captures each country’s efficiency in mobilizing taxes relative to its potential. The analysis reveals wide disparities: Cambodia shows remarkable improvement, while Malaysia and Indonesia exhibit declining trends. Key determinants include GDP per capita, trade openness, and agricultural share, with financial development (measured by banking sector credit) emerging as a critical enabler of effective tax administration. The findings suggest that expanding the VAT base, enhancing financial inclusion, and strengthening tax-financial sector linkages can significantly improve revenue mobilization and fiscal resilience in the region.